Insulinoma - The Approach to the Diagnosis, Based on a Case Report - Palma, Carolina; Antunes Pereira, Ricardo; Eliseu, António; Casimiro, Hugo Jorge; Navarro Barragan, Beatriz; Parreira, Mário; Antunes, Carla (International Journal of Innovative Research in Medical Science, 2022)
Insulinoma is the most common cause of endogenous hyperinsulinism. Most are benign and solitary. Hereby the authors present a 36-year-old woman who was admitted for confusion, aggressive behaviour, and visual hallucinations. Initial investigation revealed hypoglycaemia, and the patient recovered after the administration of intravenous glucose. The 72-hour fasting test was compatible with hyperinsulinism. Endoscopic ultrasound detected a nodule in the tail of the pancreas. Surgical resection of the nodule was performed, and histological examination revealed a pancreatic neuroendocrine tumour. The patient had a favourable outcome with resolution of the symptoms.